2021
DOI: 10.7717/peerj.11496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential gene signatures associated with osteosarcoma by integrated bioinformatics analysis

Abstract: Background Osteosarcoma (OS) is the most primary malignant bone cancer in children and adolescents with a high mortality rate. This work aims to screen novel potential gene signatures associated with OS by integrated microarray analysis of the Gene Expression Omnibus (GEO) database. Material and Methods The OS microarray datasets were searched and downloaded from GEO database to identify differentially expressed genes (DEGs) between OS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Then, we performed a receiver operating characteristic (ROC) analysis using TCGA database to evaluate the diagnostic value of hub genes ( Jia et al, 2021 ). Usually, the AUC value > 0.85 showed a good diagnostic value for lung cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we performed a receiver operating characteristic (ROC) analysis using TCGA database to evaluate the diagnostic value of hub genes ( Jia et al, 2021 ). Usually, the AUC value > 0.85 showed a good diagnostic value for lung cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The rise of throughput sequencing technology helps clarify disease-causing genes, explore disease pathogenesis, develop biomarkers, and profoundly change our understanding of biology and human diversity 5 . Researchers have developed many statistical models that use genomic data to accurately predict whether the prognostic risk of cancer patients is high or low 6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed many statistical models that use genomic data to accurately predict whether the prognostic risk of cancer patients is high or low 6 10 . Many researchers have screened multiple biomarkers related to OS by mining gene expression data 5 . Gene signature can contain more than one single gene with a unique characteristic pattern of gene expression resulting from an altered or unaltered biological process or pathogenic medical condition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that METTL7A affected the survival ability and osteogenic differentiation of BMSCs by affecting the methylation status of some related genes (Lee et al, 2021). METTL7A is also a tumor suppressor gene with decreased expression in osteosarcoma (Jia et al, 2021). Moreover, these gene expressions were detected by real-time RT-PCR and western blot.…”
Section: Discussionmentioning
confidence: 99%
“…An existing study indicates that miR-6807-5p mainly involved in the inflammatory process by downregulating drug metabolism cytochrome P450 (Kugler et al, 2020). In addition, miR-6807-5p was also one of the biomarkers of gastric cancer (Iwasaki et al, 2019). However, the role of miR-6807-5p in odontogenic differentiation of DPSCs has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%